In the second degree : paratextual literature in ancient Near Eastern and ancient Mediterranean culture and its reflections in medieval literature - Alexander, Philip S.; Lange, Armin, 1961-; Pillinger, Renate. (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2010, ISBN: 9789004222731., 2010)
To better understand the phenomenon of Literature in the Second Degree - in Jewish and Biblical studies often characterized as parabiblical or Rewritten Bible - the current volume applies the theories of Gerard Genette to ancient and medieval literature from various cultures. Literature in the Second Degree realigns earlier (authoritative) texts to the dynamics of developing cultures and their changing cultural memories. In the case of authoritative base texts, Literature in the Second Degree reaffirms their authority by way of interpretative actualization. In the case of non-authoritative base texts it replaces them to effect cultural forgetting. Far from being just literary forgery (pseudepigraphy), Literature in the Second Degree has an important function in the development of the ancient and medieval cultures.